The processes of cellular growth, aging, and programmed cell death are involved in lifespan of ovarian granulosa cells during short-term IVC - Study based on animal model - Kulus, Magdalena; Kranc, Wiesława; Sujka-Kordowska, Patrycja; Mozdziak, Paul; Jankowski, Maurycy; Konwerska, Aneta; Kulus, Jakub; Bukowska, Dorota; Skowroński, Mariusz; Piotrowska-Kempisty, Hanna; Nowicki, Michał; Kempisty, Bartosz; et al. (Theriogenology, 2020)
The oogenesis and folliculogenesis are closely linked and occur simultaneously in the growing ovarian follicles. Biochemical and morphological changes in oocytes (OC) and surrounding granulosa cells (GCs) are highly complex and depend on many factors, including intercellular communication. GCs are cells with many functions, often crucial for the proper viability of the oocyte and subsequent positive fertilization. The purpose of this study was to analyze gene expression in porcine GCs, to define differentially expressed genes belongs to the "cell growth", "aging", "positive regulation of cell death", "apoptotic process", "regulation of cell death", "cell death" and "negative regulation of cell death" ontology groups during the short - term primary in vitro culture. Microarrays were employed to study the transcriptome contained in the total RNA of the cultured GCs. Ovaries were obtained after slaughter, from 40 gilts of swine aged 170 days. The cells were obtained through puncture of the ovaries, collection of follicular fluid, removal of the cumulus - oocyte complexes and centrifugation. The cells were then cultured in vitro. The RNA material was obtained before the culture was established (0h) and then after 48h, 96h and 144h of its course. From 182 differently expressed genes belonging to the these ontology groups, we have selected POSTN, FN1, FMOD, ITGB3, DCN, SERPINB2, SFRP2, IGFBP5, EMP1, and CCL2 which were upregulated, as well as DAPL1, ESR1, IHH, TGFBR3, PPARD, PDK4, TXNIP, IFIT3, CSRNP3, and TNFSF10 genes whose expression was downregulated during the time of in vitro culture of the GCs. The significance of the differential gene expression is to provide new information on the molecular aspects of in vitro granulosa cell culture.
Keywords: folikulární buňky; kultivované buňky; Primary culture; Up-Regulation; apoptóza; upregulace; transkriptom; Gene Expression Regulation; down regulace; Pig; Transcriptome; Microarray; Down-Regulation; regulace genové exprese; Cells, Cultured; Swine; Ovarian follicle; Granulosa cells; čipová analýza proteinů; ženské pohlaví; zvířata; viabilita buněk; Cell Survival; Granulosa Cells; prasata; Female; Protein Array Analysis; Apoptosis; Animals